4.1k views
5 votes
3/7 p= -6
solve for p!
please help!

User Akalanka
by
5.7k points

2 Answers

4 votes

The goal is to isolate the variable p, right?

Lets write this out:

3/7 p = -6

We need to move 3/7 to the other side so that p can be isolated, lets do that.

3/7 ÷ 3/7 p = -6 ÷ 3/7

How does this work? Why did I do it to both sides?

When I divided 3/7 by 3/7 they canceled out, because whenever you divide something by itself it equals 1.

I divided -6 by 3/7 because because there is an equal sign, and a rule of thumb is that whatever you do on one side of the equation, you do to the other.

Now we have the equation:

p = -6 ÷ 3/7

therefore p = -14

Hope I was of use.

Cheers,

User Sachin Mhetre
by
4.7k points
3 votes

Hello,

p = -6 * 7 / 3 = -14


User CuriousSuperhero
by
5.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.